Planificación urbana y accesibilidad para personas mayores en la ciudad de Ituiutaba, MG - algunas reflexiones interdisciplinarias - Gonçalves, Geisa Candida da Silva (2019)
Urban planning establishes the spatial conditions in which individual-space relations develop. This study addresses issues related to the accessibility of three social spaces for the elderly in Ituiutaba, Minas Gerais State, Brazil: “Mário Natal Guimarães Square”, “José João Dib Avenue” walking trail and “Ituiutaba Clube” Recreational and Sports Society. The interdisciplinary reflections developed here demonstrate that the structural conditions for accessibility and use of the elderly present deficiencies as foreseen by NBR 9050, not offering adequate conditions for walking, impairing the spatial and social relations of the elderly. There was a need for supervision, readjustment and structural maintenance.